The very C-terminus of protein kinase Cε is critical for the full catalytic competence but its hydrophobic motif is dispensable for the interaction with 3-phosphoinositide-dependent kinase-1 B - Zhu Yimin (2014)
10.1016/j.cellsig.2005.07.005